2021
DOI: 10.3390/vaccines9020141
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Human Plasmacytoid Dendritic Cell-Based Vaccine to Prime and Expand Multispecific Viral and Tumor Antigen-Specific T-Cells

Abstract: Because dendritic cells are crucial to prime and expand antigen-specific CD8+ T-cells, several strategies are designed to use them in therapeutic vaccines against infectious diseases or cancer. In this context, off-the-shelf allogeneic dendritic cell-based platforms are more attractive than individualized autologous vaccines tailored to each patient. In the present study, a unique dendritic cell line (PDC*line) platform of plasmacytoid origin, already used to prime and expand antitumor immunity in melanoma pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Although this therapeutic strategy does not require the isolation of autologous pDCs and the number of pDCs is not a limiting factor, vaccination with this pDC line has been restricted to HLA-A*02:01 patients. In this regard, to improve this pDC line and to make it more widely available, its transduction with retroviral vectors encoding new HLA molecules has been tested recently [ 82 ]. Efficient transduction (~80%) was feasible without compromising functionality and cell state, and these transduced cells showed antigen-presentation capacities through acquired HLA molecules.…”
Section: Pdc-based Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Although this therapeutic strategy does not require the isolation of autologous pDCs and the number of pDCs is not a limiting factor, vaccination with this pDC line has been restricted to HLA-A*02:01 patients. In this regard, to improve this pDC line and to make it more widely available, its transduction with retroviral vectors encoding new HLA molecules has been tested recently [ 82 ]. Efficient transduction (~80%) was feasible without compromising functionality and cell state, and these transduced cells showed antigen-presentation capacities through acquired HLA molecules.…”
Section: Pdc-based Cancer Immunotherapymentioning
confidence: 99%
“…The same strategy has been used to generate pDCs that endogenously express antigens of interest. Interestingly, pDCs expressing the antigens of interest by viral transduction were able to trigger the in vitro expansion and activation of antigen-specific T cells, although higher frequencies of specific T cells were observed using passively loaded pDCs compared to transduced pDCs [ 82 ].…”
Section: Pdc-based Cancer Immunotherapymentioning
confidence: 99%
“…Given the afore-mentioned advantages of NeoAgs in vaccine approaches, we have exploited the PDC*vac platform in order to activate NeoAg-specific immune response using the same methodology as previously described [ 58 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“… CD8+ T-cells were purified from the blood of 3 healthy donors (HD#01, HD#02, HD#03) and cocultured with peptide-loaded PDC*line cells during 3 weeks with weekly restimulation at D7 and D14, as detailed in Lenogue et al [ 58 ]. Antigen-specific CD8+ T-cells (ASTC) were measured before (D0) and at different time points during coculture using multimer labeling.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have recently demonstrated that the PDC∗line transduced with genes encoding whole viral or tumoral proteins can efficiently process the transduced antigens and stably present antigen-derived peptides to specific CD8+ T cells in the context of the different HLA molecules expressed by PDC∗line cells [46 ▪ ]. The transduction of constructs encoding polyepitopes led to a multispecific CD8+ T-cell response, thereby diversifying the nature of cytotoxic effectors to potentiate the vaccine effect.…”
Section: Introductionmentioning
confidence: 99%